2018
DOI: 10.3390/ijerph15020256
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of Different Lifestyle Factors to Health-Related Quality of Life in the Elderly

Abstract: Much of the previous literature has studied the relationship between individual lifestyle factors and the health-related quality of life (HRQOL). However, only a few studies combined them to explore their relative importance to the HRQOL in the elderly. This study assesses the HRQOL of the urban, rural, and institutionalized Chinese elderly and explores the relative contributions of different lifestyle factors to their HRQOL. The SF-36v2 Health Survey, the WHOQOL-OLD module, and the socio-demographic and lifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Given the aging global population, health behaviours are important in reducing health care costs and maintaining quality of life [24]. Concerningly, adherence to recommended health behaviours was particularly low in early-middle adulthood; an important phase of disease prevention and weight management.…”
Section: Discussionmentioning
confidence: 99%
“…Given the aging global population, health behaviours are important in reducing health care costs and maintaining quality of life [24]. Concerningly, adherence to recommended health behaviours was particularly low in early-middle adulthood; an important phase of disease prevention and weight management.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, there is a positive correlation between income and health outcomes [8]. A considerable body of income-health related research suggested that better health favors higher-income groups [9][10][11]. Increasing income inequality affects the health status of the population overall [12].…”
Section: Introductionmentioning
confidence: 99%
“…The joint effect of social, physical, and mental health on HRQOL has been evidenced in studies conducted outside the Latin American region. For example, X. Zhang and colleagues (2018) found that different lifestyle factors (e.g., diet, sleep, exercise, labor, and leisure time) contributed to the perception of HRQOL in Chinese older adults.…”
Section: Discussionmentioning
confidence: 99%